HAMBATAN PELAKSANAAN KRITERIA KETUNTASAN MINIMAL MATA PELAJARAN PRODUKTIF TATA BUSANA SMKN 1 LEMBAH GUMANTI - Margareta, Mia; Katin, Yusmar Emmy; Nazar, Ernawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This study aims to describe the implementation of Productive KKM dressmaking courses in SMKN 1 Gumanti Valley, in terms of the criteria for determining the KKM intake (student ability), complexity (difficulty level indicator), and carrying capacity. This research is qualitative research. Subject and informant research is Professor Earning dressmaking, amounting to 5 (five) people. Data collection techniques are observation, interviews, documentation, and triangulation. Data processing techniques are data collection, data reduction, data display, and conclusion. The results of this study indicate the general implementation of the Productive subjects KKM dressmaking, where teachers are still having difficulty, namely the intake criteria (student ability), On the criteria of complexity where teachers are difficult to adjust the complexity of the material with the ability of students. As well as carrying on the criteria, lack of educational infrastructure that supports the learning process, and the number of teachers earning dressmaking that do not meet the ideal standards.